Education and assistance in hydroponic plant cultivation for strengthening the self-reliant economy - Septi Budi Sartika; Chandrika Rahmania Cahyani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Assistance with a hydroponic cultivation theme towards strengthening the self-reliant economy of Sukoreno Village is a manifestation of awareness in contributing to the development of a more modern agricultural system and Micro, Small, and Medium Enterprises (MSMEs) within the community. The partners for this activity are 10 members of the Sukoreno Village Youth Organization ("karang taruna"). The implementation method consists of three stages: planning, implementation, and evaluation. During the planning stage, the situation and potential of the Sukoreno Village community are analyzed. In the implementation phase, seminars are conducted to provide information and invite the local youth organization and village government officials to practice farming using hydroponic systems, which are more space-saving, environmentally friendly, and practical to maintain. This aims to raise awareness among the community that farmers do not always have to rely on large plots of land. Evaluation involves regular checks on the hydroponic growing media in the village's greenhouse. Based on the monitoring and assistance activities conducted by our group members, the cultivated plants have thrived and become assets for the village's youth organization. Furthermore, some residents have shown interest in practicing hydroponics in their own homes. This activity can be further expanded on a larger scale within the Sukoreno Village area.